Preferensi Pesan Budaya Dalam Fotografi Budaya : Analisisi Isi Karya Fotografi Budaya Pada Akun Instagram @iswahyura05 - Wasisa, Iswahyura Putra; Faris, Faris (Prisani Cendekia Institute, 2025)
Cultural photography has visual value and deep meaning in every moment. Indonesia is a country with diverse cultures in each region, where cultural photography plays an important role in preserving and sustaining culture by capturing every cultural moment in Indonesia. This study aims to explore cultural message preferences in cultural photography on the Instagram account @iswahyura05. The methodology used is Content Analysis with a quantitative approach, aimed at capturing cultural message preferences in cultural photography on the Instagram account @iswahyura05. The research findings indicate that from the total 100% of the samples analyzed, which have been adjusted to several predetermined categories, the researcher found that cultural photography works on the Instagram account @iswahyura05 lean more towards the category related to art, with a percentage of 40%.